2017
DOI: 10.3748/wjg.v23.i9.1657
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a novel slim type FlushKnife-BT over conventional FlushKnife-BT in esophageal endoscopic submucosal dissection

Abstract: AIMTo investigated the usefulness of a novel slim type ball-tipped FlushKnife (FlushKnife-BTS) over ball-tipped FlushKnife (FlushKnife-BT) in functional experiments and clinical practice.METHODSIn order to evaluate the functionality of FlushKnife-BTS, water aspiration speed, resistance to knife insertion through the scope, and waterjet flushing speed were compared between FlushKnife-BTS and BT. In clinical practice, esophageal endoscopic submucosal dissection (ESD) performed using FlushKnife-BTS or BT by an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…These are complex therapeutic endoscopic procedures and carry a risk of collateral damage to the muscle or mucosa, especially when performed during the learning curve [12]. The technical difficulty associated with these procedures can be reduced with experience as well as through improvement in the currently available electrosurgical knives [4,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…These are complex therapeutic endoscopic procedures and carry a risk of collateral damage to the muscle or mucosa, especially when performed during the learning curve [12]. The technical difficulty associated with these procedures can be reduced with experience as well as through improvement in the currently available electrosurgical knives [4,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…In our hospital, we mainly use the FlushKnife BT-S for colorectal ESD. This knife has some merits in terms of its water jet function, which means that endoscopists can inject normal saline into the submucosal layer using the knife without the need to exchange it with other needles 8 9 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a thicker body/tube of knife is better in allowing for more liquid flow but at the expense of knife insertion time and vacuum or suction function under knife in the channel. A previous study showed a little decrease of water injection amount in the air with Flush knife BT-S (2–15 ml/min) compared to Flush knife [ 8 ]. However, in the current study using porcine stomach, the Flush knife BT-S did not show significant water jet function impairment compared to the Flush knife BT.…”
Section: Discussionmentioning
confidence: 99%
“…The novel narrow ESD knife (Flush knife BT-S 2.0 mm, diameter: 2.2 mm, Fujifilm Co., Tokyo, Japan) and the knife with regular diameter (Flush knife BT 2.0 mm, diameter: 2.6 mm, Fujifilm Co., Tokyo, Japan) were utilized in this study ( Figure 1() ) [ 8 ]. With respect to the diameter of the Flush knife BT-S, it is a slim design but with only the front 3 cm tip part made slightly thick (2.6 mm) to anchor and ensure stable movement of the knife during dissection.…”
Section: Methodsmentioning
confidence: 99%